Relationship of Fibroblast Growth Factor 23 With Retinopathy of Prematurity Severity in Preterm Infants - Yusupov A.F.; Karimova M.Kh.; Usmanova Y.A. (International Journal of Medical Sciences And Clinical Research, 2025)
Relevance. Retinopathy of prematurity (ROP) is among the primary causes of childhood blindness, particularly in countries with well-developed neonatal care systems. Emerging evidence points to the importance of hormonal regulators in angiogenesis, including fibroblast growth factor 23 (FGF23). However, its role in the pathogenesis of ROP remains poorly understood. Objective. To evaluate the association between serum FGF23 levels in the early neonatal period and the severity of ROP in infants born at a gestational age of less than 32 weeks. Materials and Methods. This study involved 38 preterm infants: 18 with confirmed ROP (main group) and 20 without signs of ROP (control group). All participants underwent ophthalmological assessment according to the ICROP-3 (2021) and ETROP classification systems. Serum FGF23 levels were measured by chemiluminescent immunoassay (CLIA) from umbilical cord blood collected immediately after birth. Results. The mean serum FGF23 concentration was significantly higher in the ROP group compared to controls (p<0б001). A strong positive correlation was identified between FGF23 levels and ROP severity (r=0б71). Elevated FGF23 levels may contribute to the pathophysiology of ROP in preterm infants and could serve as a potential early biomarker for identifying those at risk of developing severe disease.